MCPHERSON, A.K Inventory of documents - MCPHERSON, A.K (ARCA, 2018)
Private papers of A.K. McPherson, publisher of the Queenstown Daily Representative and Free Press, taken over by the Daily Dispatch in 1921 and McPherson became one of the Directors [1921-1956]. President of the Press Union [1928-1929].
COVERAGE 1938-1966, 5 Files; 0.11 metre
Keywords: MCPHERSON, A.K; Journalist